Interculturalidade e prática docente Pataxó - Folegatti, Carla Viviani Silveira (Universidade Federal de São Carlos, 2020)
This research aims to investigate the pedagogical practices of teachers at the Pataxó Boca da Mata Indigenous School, TI Barra Velha, Porto Seguro, Bahia, in the possibility of understanding how intercultural proposals are presented in this context and how they contribute with the community involved. As a way to achieve the proposed objectives, the research was defined as qualitative, carried out through a unique case study, theoretically based on the proposals for intercultural education in the Latin American context and characterized as a space for the struggle of indigenous peoples for social justice, a place of affirmation of identity, resistance, recognition and movement. As a case study, the research used semi-structured interviews and discussion group for data collection, being the objectives, to understand the concepts of interculturality and the possibilities and obstacles of the proposals present in the individual and collective teaching practices; analyze the relationship of dialogue between scientific knowledge and traditional knowledge and; investigate with teachers the depth and complexity of their contributions to the process of recognition, autonomy and cultural preservation of their community.
Interculturality and teaching pratice Pataxó
Keywords: Educação escolar indígena; Interculturalidade; Autonomia; Reconhecimento; Preservação cultural; Indigenous school education; Interculturality; Autonomy; Recognition; Cultural preservation; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO